Evaluación de dosis creciente del extracto de moringa moringa oleifera sobre mycosphaerella fijiensis bajo condiciones de campo y laboratorio - Morales Morocho, Freddy Hjalmar (2017)
The present investigation was carried out in a banana template Of the cultivar Williams 3 months old , With 5 functional leaves of the Williams cultivar; In the experimental farm "Santa Inés" belonging to the Academic Unit of Agricultural Sciences, Technical University of Machala, Due to the problems presented by the Disease known as Black sigatoka (SN) In banana cultivation Caused by fungus Mycosphaerella fijiensis M., produces Yield loss of between 50 and 100%, significantly affecting the producer's economy. This disease mainly attacks the leaves, producing a rapid deterioration of the leaf area when it is not fought, it also affects the growth and productivity of plants by reducing the capacity of photosynthesis. It also produces a reduction in the quality of the fruit, by favoring the maturation of the bunches and therefore reduces their production. Therefore, the need arises to find new alternatives to control the SN, The botanical extracts being a source of compounds with a biocidal effect and being environmentally friendly, showing positive results to combat diseases caused by microorganisms, guaranteeing a more sustainable and less polluting agricultural production. For these reasons, the response of SN (Mycosphaerella fijiensis) To the application of increasing dose of leaf extract Moringa oleifera, Therefore it was proposed as general objective: To evaluate the effect of extract of the leaf of moringa in the control of the Black Sigatoka (Mycosphaerella fijiensis Morelet) in the cultivation of bananas. Banana leaves infected with the fungus were collected Causing the SN (Mycosphaerella fijiensis M.), was isolated in-vitro using PDA (Potato agar and dextrose), Evaluating the different concentrations of the extract. He In vitro assay was performed with 6 treatments Y 6 replicates, taking as a variable, the radial growth of the mycelium of the fungus Mycosphaerella fijiensis M., the doses evaluated were T1 (1%), T2 (3%), T3 (5%), T4 (10%), T5 (Mancozeb) and T6 (Control). A completely randomized design (DCA) was used. Variables Valued Every 10 days after inoculation over a period of 20 days. According to the results obtained the dose that presented or An antifungal effect is T4 (10%). In the field phase, A single application of the extract for each treatment in leaves 1 and 2, Who will later change their position. He Trial was performed with 6 treatments and 12 repetitions, taking as variables, The number of pinches and the area under the curve of disease progression (AUDPC). The evaluated doses were: T1 (1%), T2 (3%), T3 (5%), T4 (10%), T5 (Mancozeb) and T6 (Control). Statistical analysis used a parametric ANOVA (Tukey 95%) And completely randomized block design (DBCA). Variables Evaluated Weekly to the mind Began to 35 to 63 days after the application of the leaf extract Moringa oleifera. According to the results Obtained The T4 (10%) presented a lower AUDPC and therefore a better control.